Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.14295/oh.v25i2.2013
|View full text |Cite
|
Sign up to set email alerts
|

Study of natural ventilation in a Gothic multi-tunnel greenhouse designed to produce rose (Rosa spp.) in the high-Andean tropic

Abstract: In tropical regions the production of ornamentals is developed exclusively in naturally ventilated plastic greenhouses, which sometimes leads to inappropriate microclimates with high temperatures and humidity that limit the productive development of plants. The aim of this work was to study air flows, temperature distribution and relative humidity inside an alternative greenhouse designed to produce rose (Rosa spp.). Three configurations of ventilation, side ventilation (SV), roof ventilation (RC) and combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
2
15
0
2
Order By: Relevance
“…For the temperature variable, it was found that the MAE value oscillated between minimum and maximum values of 0.124 • C and 0.346 • C for 6:00 and 13:00 h respectively, while the RMSE values oscillated between 0.140 and 0.397 • C for these same hours. These values found are within the ranges reported in previous studies where CFD models were implemented to determine airflow patterns and thermal distribution in naturally ventilated greenhouses [34,51]. In the case of the air velocity variable inside the greenhouse evaluated, the spatial distribution of the measured and simulated values for each hour was plotted, finding that the experimentally sampled values showed high coincidence with the simulated values (Figure 6).…”
Section: Data and Validation Of Cfd Modelsupporting
confidence: 86%
See 2 more Smart Citations
“…For the temperature variable, it was found that the MAE value oscillated between minimum and maximum values of 0.124 • C and 0.346 • C for 6:00 and 13:00 h respectively, while the RMSE values oscillated between 0.140 and 0.397 • C for these same hours. These values found are within the ranges reported in previous studies where CFD models were implemented to determine airflow patterns and thermal distribution in naturally ventilated greenhouses [34,51]. In the case of the air velocity variable inside the greenhouse evaluated, the spatial distribution of the measured and simulated values for each hour was plotted, finding that the experimentally sampled values showed high coincidence with the simulated values (Figure 6).…”
Section: Data and Validation Of Cfd Modelsupporting
confidence: 86%
“…The values of the highest normalized velocity agreed with the time when the temperature of the outside environment started to decrease, therefore it can be mentioned that this acceleration of the air flow inside the greenhouse may be strongly associated with the thermal effect of natural ventilation by buoyancy; an effect that generally produces rapid changes in temperature and velocity inside a greenhouse [59]. This buoyancy phenomenon is caused by convective movements generated between the soil and the greenhouse cover, since at that time the soil is the surface of higher temperature due to energy storage throughout the day, while the cover usually cools rapidly to the level of the outside ambient temperature [34,60].…”
Section: Air Velocity Inside the Greenhouse And Calculated Ventilation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…When separating the behaviour during the day and the night, it is observed that for the night period the behaviour of the temperature inside the greenhouse was similar to that of the temperature outside, obtaining values of 11.6 and 11.5 °C respectively, on the other hand, for the day period the average value of the temperature inside was 16.9 °C while in the outside 2A). The daytime thermal behaviour can be considered acceptable for rose production between 9 and 16 hours where the temperature value is above the minimum recommended value of 17 °C for rose production, but well below the recommended optimum value of 24 °C, this will result in longer growing cycles (Villagrán and Bojacá, 2019a). It should also be noted that the thermal behaviour at night is not suitable for the production of roses as they have average values of less than 12.5 °C inside the greenhouse, which is below the minimum recommended value for rose production of 14 °C (Reid, 2008).…”
Section: Temperaturementioning
confidence: 99%
“…Las distribuciones espaciales de temperatura y humedad relativa sobre la zona de cultivo en cada una de las estructuras estudiadas mostraron un comportamiento que se puede considerar homogéneo, ya que las diferencias entre los valores máximos y mínimos para cada hora simulada fueron mínimos. Lo anterior se concluye al comparar los resultados de esta investigación con los resultados obtenidos en otros estudios de invernaderos y casa de malla donde para un momento de tiempo específico se reportan diferencias entre zonas en el interior de las estructuras con valores superiores a los 4°C para la temperatura y 15% para la humedad relativa (Flores-Velazquez, Guerrero, López, Montero, & Piscia, 2013;Mesmoudi et al, 2017;Villagrán & Bojacá, 2019b).…”
Section: Discussionunclassified